The impact of institutional transformations on MNEs entrepreneurship in emerging economies - Xanthippe Adamoglou; Yannis Hajidimitriou (SPOUDAI - Journal of Economics and Business, 2021)
This paper examines how an emerging economy's institutional context motivates different forms of MNE entrepreneurship, which, subsequently, leads either to economic development or economic growth. To do so, the paper distinguishes emerging economies' institutional environment into a state of stable conditions and a state of crisis and i t reconciles such a distinction with Cantwell's et al. (2010) coevolution framework. Secondary statistic data, in conjunction with the appreciative method, have been applied to test the three hypotheses developed. Results reveal that in the periods 1990-2001 and 2008-2011 institutional avoidance and adaptation took place. In the period 2002-2007 institutional coevolution emerged, while in the period 2012-2016 institutional avoidance prevailed.
Keywords: L22; L24; 330; Multinational enterprises; emerging economies; FDI; institutional development; economic development; economic growth